DC method for self-heating estimation applied to FinFET - Mori, C. A.B. [UNESP]; Agopian, P. G.D.; Martino, J. A. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This paper reports an extension on the application of the DC method for the estimation of self-heating effects from planar to FinFET devices, verified through theoretical considerations and numerical simulations. In the worst case, a difference of 5.6% was observed on the estimation of the transistors channel temperature when compared to a traditional method.
Keywords: FinFET; Self-heating effect; Semiconductor-On-Insulator